Simulation and Cost-Effectiveness Analysis of New York's Emergency Ambulance Service - Savas, E. S. (Management Science, 1969)
Computer simulation was used to analyze the possible improvements in ambulance service that would result from proposed changes in the number and location of ambulances. The cost-effectiveness of several alternatives was examined. A particular alternative was shown to be of considerable value and it was concluded that low-cost improvements in service could indeed be achieved by redistributing ambulances in accordance with this alternative. This marks the first time that the City of New York has utilized computer simulation as an aid to decision-making. In addition, this represents another step in the move to use computers more creatively in municipal management. More generally speaking, the notion of applying the “space-age methods” of systems analysis, operations research, cost-effectiveness analysis, etc., to solve urban problems is a very popular one, frequently written about, discussed, and presented at conferences. The work reported here has translated this concept into practical results in a vital area of public service. This is a small but significant advance, of potential value to urban governments everywhere.